2002
DOI: 10.4141/p01-034
|View full text |Cite
|
Sign up to set email alerts
|

Breeding potential of the backcross progenies of a hybrid between Trifolium medium × T. pratense to T. pratense

Abstract: Breeding potential of the backcross progenies of a hybrid between Trifolium medium × × T. pratense to T. pratense. Can. J. Plant Sci. 82: [395][396][397][398][399]. In this study, T. medium (zigzag clover, 2n = 80 and T. pratense (red clover, 2n = 28) were hybridized and backcrossed four times to T. pratense (BC 1 , BC 2 , BC 3 and BC 4 ), and the seed production and vigor of the backcross progenies were assessed under field conditions. Both female and pollen fertility of the backcross progenies increased as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 5 publications
2
22
0
Order By: Relevance
“…In contrast to the fifth generation (Řepková et al 2003), the majority of plants today possess 2n = 28 chromosomes. This shows a strong tendency to stabilize the unbalanced genomes into the maternal state, as was previously reported also in clover (Isobe et al 2002) as well as in other crop plants (RennyByfield & Wendel 2014). Aside from plants with 2n = 28 chromosomes, a significant proportion of differing chromosome counts dissimilar to both parents was recognized in both generations (24.0% in JEH1V and 34.3% in JEH1F).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In contrast to the fifth generation (Řepková et al 2003), the majority of plants today possess 2n = 28 chromosomes. This shows a strong tendency to stabilize the unbalanced genomes into the maternal state, as was previously reported also in clover (Isobe et al 2002) as well as in other crop plants (RennyByfield & Wendel 2014). Aside from plants with 2n = 28 chromosomes, a significant proportion of differing chromosome counts dissimilar to both parents was recognized in both generations (24.0% in JEH1V and 34.3% in JEH1F).…”
Section: Resultssupporting
confidence: 79%
“…The only examination was performed on the fifth hybrid generation by means of flow cytometry measurement, which showed DNA content corresponding to the range of 30-45 chromosomes (Řepková et al 2003). Subsequent hybrid generations were not examined at all and their genetic states have so far remained unknown, even though the previous reports of clover hybrids had observed genomic instability among successive generations leading to the loss of chromosomes (Isobe et al 2002).…”
mentioning
confidence: 99%
“…In our opinion, the prevailing dominance of T. pratense traits in hybrids is a consequence of repeated backcrosses. This corresponds to the results of Isobe et al (2001), who observed different leaf morphologies between BC 4 plants and T. pratense in the same cross combination in comparison with the parental species. The intermediate morphological appearance of interspecific hybrids was also observed in other species combinations, such as T. alexandrinum × T. apertum , T. alexandrinum × T. constantinopolitanum and T. alexandrinum × T. resupinatum (Kaushal et al 2005).…”
Section: Discussionmentioning
confidence: 91%
“…T. pratense has been successfully crossed with five species so far (reviewed by Abberton 2007): T. sarosiense Hazsl. (Collins et al 1981;Phillips et al 1982), T. medium L. (Collins et al 1981;Vogt & Schweiger 1983;Merker 1984;Sawai et al 1990;Isobe et al 2002;Nedbalkova et al 1995), T. alpestre L. (Collins et al 1981;Merker 1988;Phillips et al 1992), T. ambiguum M.Bieb. (Vogt & Schweiger 1983) and T. diffusum Ehrh.…”
Section: Wide Hybridizationmentioning
confidence: 99%